Are we saying it right? Communication strategies for fighting vaccine hesitancy - Di Lorenzo, Antonio; Stefanizzi, Pasquale; Tafuri, Silvio (Frontiers in Public Health, 2024)
Vaccine hesitancy is a multi-faceted phenomenon, deeply rooted in cultural, socioeconomic and personal background. Communication is deemed fundamental in fighting vaccine hesitancy. Medical communication should be accessible, relying both on an emotional approach and accurate information. Trained professionals should curate communication with the public.